INHIBITOR PERTUMBUHAN Pyricularia oryzae DENGAN EKSTRAK CAIR DAUN PRONOJIWO (Euchresta horsfeildii) SECARA IN VITRO - Astini Astini; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2017)
Has been done research that aims to test the inhibitory power of pronojiwo (Euchresta horsfieldii) leaf extract to the fungus P.oryzae. the experimental study was conducted using a completely randomized design with 9 concentrations of liquid extract of pronojiwo leaf and 1 control. Ie the concentration of each pepeated 4 times and in duplo. Application is done by the method of well by means of liquid extract dripped on the diffusion well, dilusion method by means of liquid extract mixed on the media PDA, method of calculating the amount of fungus conidia by means of liquid extract mixed with media PDB, to determine the inhibition zone of the fungus, the growth of the diameter of the fungus, the number of living conidia. Observations were made after incubation for 7 days. The results showed that liquid extract pronojiwo leaves can inhibit and reduce the growth of fungus P.oryzae, at a concentration of 6,25% with a resistor zone result of 0,9 mm, a growth diameter percentage of 71,2%, and may reduce by 2,9 conidia/ml. Keywords : pronojiwo leaves, growth, reduce , fungus P.oryzae